1999
DOI: 10.1038/12497
|View full text |Cite
|
Sign up to set email alerts
|

Painful stimulation suppresses joint inflammation by inducing shedding of L-selectin from neutrophils

Abstract: Although the inflammatory response is essential for protecting tissues from injury and infection, unrestrained inflammation can cause chronic inflammatory diseases such as arthritis, colitis and asthma. Physiological mechanisms that downregulate inflammation are poorly understood. Potent control might be achieved by regulating early stages in the inflammatory response, such as accumulation of neutrophils at the site of injury, where these cells release chemical mediators that promote inflammatory processes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…L-selectin (CD62L) facilitates rolling and temporary arrest of circulating leukocytes on endothelium surface [53], whereas β2-integrin (CD11b) is involved in subsequent stable adhesion [54,55]. Therefore, therapeutic approaches to reduce expression of CD62L and CD11B have been important strategies to prevent vaso-occlusion in sickle cell disease [50].…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin (CD62L) facilitates rolling and temporary arrest of circulating leukocytes on endothelium surface [53], whereas β2-integrin (CD11b) is involved in subsequent stable adhesion [54,55]. Therefore, therapeutic approaches to reduce expression of CD62L and CD11B have been important strategies to prevent vaso-occlusion in sickle cell disease [50].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of adhesion molecules on the surface of BAL-derived leukocytes may be important in cell communication and activation, and account for functional differences between BAL-derived and peripheral blood cells. Entry of PMN into inflamed tissue requires L-and P-selectin activity [16], and increased CD62L shedding has been suggested to have inhibitory effects on PMN adhesion and transmigration across endothelium, thus reducing PMN recruitment [17]. Thus, down-regulation of CD62L on PMN by feG may have a role in reducing PMN numbers in the lungs of OVAchallenged rats.…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin has been implicated in several steps during neutrophil recruitment to inflammatory sites: tethering and rolling of the neutrophil on the endothelium (49), neutrophilneutrophil interactions (50), activation of intracellular signaling pathways (51), and extravascular migration (52). Previous studies have shown that modulation of L-selectin levels via shedding can have a marked impact on neutrophil-endothelial interactions (16,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that administration of glucocorticoids to humans and animals induces L-selectin shedding on peripheral blood neutrophils (11)(12)(13)(14). In addition, our previous work has shown that inhibition of L-selectin-dependent plasma extravasation is blocked by both adrenalectomy and a glucocorticoid synthesis inhibitor (15,16). However, when neutrophils are treated in vitro with doses of glucocorticoids that produce L-selectin shedding in vivo, shedding is not observed (17)(18)(19).…”
mentioning
confidence: 91%